-3x-8+x=-4x+-10

Simple and best practice solution for -3x-8+x=-4x+-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-8+x=-4x+-10 equation:


Simplifying
-3x + -8 + x = -4x + -10

Reorder the terms:
-8 + -3x + x = -4x + -10

Combine like terms: -3x + x = -2x
-8 + -2x = -4x + -10

Reorder the terms:
-8 + -2x = -10 + -4x

Solving
-8 + -2x = -10 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-8 + -2x + 4x = -10 + -4x + 4x

Combine like terms: -2x + 4x = 2x
-8 + 2x = -10 + -4x + 4x

Combine like terms: -4x + 4x = 0
-8 + 2x = -10 + 0
-8 + 2x = -10

Add '8' to each side of the equation.
-8 + 8 + 2x = -10 + 8

Combine like terms: -8 + 8 = 0
0 + 2x = -10 + 8
2x = -10 + 8

Combine like terms: -10 + 8 = -2
2x = -2

Divide each side by '2'.
x = -1

Simplifying
x = -1

See similar equations:

| c/4=16 | | x-(-12)=2 | | 2(x+10)-5(2-x)+3=0 | | 81-4x^2=0 | | x-(-8)=-28 | | (x^2-11+19-x)(-10)= | | (3x-5)+(3x+5)+x=180 | | 4m^3-9=23 | | x-(-1)=50 | | 3.2b+8=20 | | 2+6x-3-3x=0 | | 22=4(5y-2) | | x-(-5)=10 | | x+(x+5)+x+(x+5)=26 | | 19=17-2x | | 9-5t=3t+18 | | 5x+4=13x-68 | | 9x^2+16=24x | | 3p^2+5=32 | | 19x-7=1+17x | | Q=650-5P-P^2 | | 9-5t=3t+21 | | 8x+6=3x | | 5(6-4x)=25 | | 7+5q=9+4q | | p(x)=3x^4-4x^3-6x^2+20x-16 | | 7-3x=3(3x)-2 | | Qd=650-5p-p^2 | | 5x=4x+11 | | 22-0.5q-P=0 | | 6x-14=46 | | 3n-6n=9 |

Equations solver categories